Business continuity management for an agribusiness company: a case study from west Africa - Mouphtaou, Tene (Kansas State University, 2014)
The overall objective of this research is to develop a business continuity plan for a relatively large livestock company located in Francophone West Africa. This is very important in an environment when both internal and external risks can lead to significant disruptions in the business processes. The research, thus, focuses on developing a process that can be applied to establish a business continuity management process in this firm and provides the framework for implementing such a plan successfully. The livestock company, let us call it Livestock Co. to protect its identity, wants to define strategies for recovery, resumption of business and other key activities under the potential scenarios. Its managers desire to formulate crisis response strategies that would be implemented quickly when these disasters hit. The thesis envisages the potential conditions that may trigger these crises and develops the management systems to mitigate them, returning the business to it activities as quickly as possible. Some of the natural disasters that may be considered are fire, accidents and political upheavals. Some technical disasters that may be imagined may be related to infrastructure, labor crisis, and grain dust explosions. Unlike natural disasters, which often are uncertain, technical disasters can be predicted based on careful assessment of the environment or the assets. The research evaluates the process for developing a business continuity management plan and offers an implementation process to ensure its smooth execution.
Keywords: Business continuity management; Emergency response; Risk; Crisis management; Economics (0501); Economics, Agricultural (0503); Management (0454)